AB0054 Relationship between Calprotectin Serum Level, Disease Activity, Matrix Metalloproteinase-3 Concentration and Response to Etanercept Therapy in RA Patients. (10th June 2014) - Pchelintseva, A.; Zhornyak, A.; Ionichenok, N.; Panasyuk, E.; Cherkasova, M.; Denisov, L.
Abstract : Background: Calprotectin (CP) is potentially more sensitive biomarker of disease activity in rheumatoid arthritis (RA) than conventional acute-phase reactants because it directly reflects inflammation in the synovium rather than systemic inflammation. Objectives: to evaluate relationship between serum CP levels, disease activity, matrix metalloproteinase-3 (MMP-3) concentration and response to Etanercept (ETN) therapy in RA patients. Methods: 84 patients with moderate-to-severe RA despite stable doses of cDMARDs received ETN 50 mg weekly for 24 weeks. The mean age was 52±13, 3 years; 85% (n=71) were females; the median disease duration was 9, 3±8, 3 years; RF+ and ACCP + were 81% (n=68) and 83% (n=70), extraarticular manifestations were found in 18% (n=15); 62% (n=52) used MTX, 26% (n=22)-LEF, 11% (n=9)-other DMARDs, 38% (n=32) -corticosteroids ≤10 mg/day. 60% (n=50) had used another biologics prior to start of ETN. Baseline disease characteristics (Me [Q25–75 ]): patient disease activity, VAS, mm: 63 [49-75]; TJC: 12 [9-16]; SJC: 9 [7-12]; CRP, mg/l: 23, 7 [8, 25-46, 8]; ESR, mm/h: 46 [29-67]; RF, IU/ml: 122, 5 [17, 45-313, 15]; ACCP, U/ml: 181, 2 [43, 6-300]; DAS28 6, 35 [5, 72-6, 81]; CP, μg/ml 5, 34 [2, 12-10, 98]; MMP-3, ng/ml 1, 01 [0, 64-1, 67].Response was defined as achievement of good/moderate response according EULAR at weeks 12, 25. Serum CP and MMP-3 levels were evaluated with ELISA at weeks 0, 12, 25. Serum samples from 21 healthy subjects served as control. Results: There wasn't significant difference in median CP level between patients with RA compared to healthy controls (5, 34 vs 4, 17, p =0, 26) at baseline, possibly due to small size of control group. Highly significant correlations were found in RA patients between CP baseline level and ESR, CRP, MMP-3 and DAS28 at week 0: CRP ( r =0, 69, p <0, 0001), ESR (r=0, 41, p <0, 0001), MMP-3 (r=0, 47, p<0, 0001), DAS28 ( r=0, 37, p<0, 0001). The similar data were determined at weeks 12 and 25. We didn't find strong correlations between CP level and clinical parameters of disease activity. CP serum level decreased after 6 months of ETN treatment (p<0, 0001). ROC analysis provided an AUCroc of 0.8±0, 06 (95%CI 0, 68-0, 91) for the differentiation of RA patients and healthy control. A cut-off value of 0, 67 μg/ml resulted in sensitivity and specifity values of 73 and 86% respectively.There wasn't found predictive value for CP baseline level and good/moderate EULAR response to ETN treatment (AUCroc =0, 41±0, 07; p=0, 18; 95%CI 0, 28-0, 54). Conclusions: CP level strongly correlates with laboratory parameters of joint inflammation and bone destruction (MMP-3) and significantly decreases in response to ETN treatment. There was not prognostic association between CP baseline level and response to ETN treatment. This result indicate that CP is a promising marker for assessment and monitoring of disease activity in RA patients. CP prognostic value is unclear, futher investigations are required to evaluate it. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3484